Pelatihan Pembuatan Media Pembelajaran Daring Bagi Guru SMA Menggunakan Open Broadcaster Software - sunardi sunardi; Achmad Dito; January Audrey; Rachmad Very Ananda Saputra; Syifa Riski Ardiningtias (Jurnal Nasional Pengabdian Masyarakat, 2021)
This community service program carries out training on optimizing the use of Open Broadcaster Software (OBS) in online learning, primarily due to the Covid-19 pandemic. The training is given to 16 participants of SMAIT Abu Bakar Yogyakarta teachers. This training aims to introduce supporting media that can be used in the online teaching and learning process more interactively and present it live streaming via YouTube. In the pre-test, 69% of participants had never been familiar with the term OBS. Only 19% have observed people using OBS; in fact, none (0%) have ever used OBS. After the training, participants gained additional knowledge/insight about OBS, and 94% agreed that the training that had been provided made learning more structured about OBS. Participants stated that 100% agreed that OBS could be further optimized for learning. The enthusiasm of the participants can be seen from after the training. 100% of the participants will participate again if this kind of training is held